FAKTOR – FAKTOR PENYEBAB SISA LEBIH ANGGARAN DANA BAGI HASIL CUKAI HASIL TEMBAKAU KABUPATEN KUDUS TAHUN 2009 – 2013 - Reno Fahamzah Kiswoyo; Fitriyah .; Sulistyowati . (Journal of Politic and Government Studies, 2015)
Abstract:Kudus Regency is the largest recipient of revenue sharing fund tobacco excise, in Central Java. However, the government of the Kudus Regency still having trouble in managing revenue sharing fund tobacco excise. This can be seen in the use of budget revenue sharing fund tobacco excise Kudus Regency that had suffered surplus budget from 2009 – 2013. This study used a qualitative research method, with descriptive research type. The results of these studies include, surplus budget revenue sharing fund tobacco excise Kudus Regency of the year 2009 - 2013 due to the regulatory aspects, auction factors process goods/services funded by revenue sharing fund tobacco excise, and the delay factor of revenue sharing fund tobacco excise allocation. The existence of surplus budget revenue sharing fund tobacco excise impact on the government's responsibility to manage surplus budget Kudus Regency revenue sharing fund tobacco excise in the next year. Because according to the Ministry of Finance Regulation No. 20/PMK.07/2009, surplus budget revenue sharing fund tobacco excise but not scorched into the local treasury and must be budgeted for the next fiscal year.Keywords: Fiscal Decentralization, Revenue Sharing Fund Tobacco Excise, Budget Surplus